Pengaruh Literasi Keuangan, Lifestyle Hedonis dan Sikap Keuangan Pribadi Terhadap Perilaku Keuangan - Andhika Bagas Prasetya; Entot Suhartono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Financial behavior is a person's ability to manage planning, budgeting, checking, managing, controlling, searching for and storing daily financial funds. One of the factors that influences financial behavior is knowledge of financial literacy. Financial literacy is the ability to make accurate judgments and make effective decisions about the use and management of free time. A hedonistic lifestyle is a person's lifestyle whose activities are seeking pleasure in life, spending time outside the home to have fun with friends, likes to buy unnecessary things, and always wants to be the center of attention around them. The author's goal is to determine the effect of financial literacy, hedonistic lifestyle and personal financial attitudes on financial behavior in students of the management study program, Faculty of Economics, class of 2020. The number of samples in this study was 100 students. The analysis technique in this study used multiple linear regression, determination of multiple correlations, t-test and F-test. The results of this study indicate that financial literacy (X1) has a significant effect on financial behavior (Y). Hedonistic lifestyle (X2) has no effect on financial behavior (Y). Personal financial attitudes (X3) have a significant effect on financial behavior (Y). Financial literacy, hedonistic lifestyle, and personal financial attitudes simultaneously have a significant influence on financial behavior.